The Effect of Tip Clearance Kaplan Ducted Propeller in Offshore Supply Vessel (OSV) on Hydrodynamics - Winarno, Arif; Sakti, Gedhe Angkoso Nur Sofa; Sugianto, Erik (Department of Naval Architecture - Diponegoro University, 2024)
A ducted propeller is a modification of a propeller by adding a duct or nozzle. The purpose of using a ducted propeller is to increase thrust, increase propeller efficiency, and encourage better ship movement. This is suitable for Offshore Supply Vessel (OSV) vessels operating on offshore platforms to support oil drilling activities. In designing a kort nozzle, one of the most important components is the tip clearance, the distance between the edge of the propeller and the inner nozzle. The diameter of the kort nozzle can affect the thrust efficiency of the propeller. Due to the blade momentum theory for ducted propellers, the volume of water passing through the propeller should be as large as possible, with the smallest possible flow velocity. In this study, numerical simulations using the Computational Fluid Dynamics (CFD) method were carried out to determine the effect of tip clearance on thrust and torque on a ducted propeller with a MARIN foil 19A nozzle type and tip clearance of 10 mm, 20 mm, and 30 mm. From all models, the highest thrust and torque values were obtained from the nozzle 19A tip clearance 10 mm model with thrust 367,413 kN and torque 315,338 kNm. The relationship between tip clearance and thrust is inversely proportional; the greater the tip clearance, the smaller the value of thrust, and the same is true with torque.